7A.10: METABOLIC SYNDROME PREDICTS INDEPENDENTLY FROM ITS COMPONENTS ADVERSE EVENTS IN ESSENTIAL HYPERTENSIVE SUBJECTS. (June 2015) - Georgiopoulos, G.; Tsioufis, C.; Tsiachris, D.; Dimitriadis, K.; Liatakis, I.; Kalos, T.; Andrikou, E.; Valenti, P.; Eleftheriadou, I.; Lymperopoulou, D.; Tousoulis, D.
Abstract : Objective: Metabolic syndrome (MS) is associated with increased risk for atherosclerotic cardiovascular disease, whereas its prognostic role in hypertension remains controversial. The aim of the present study was to assess the relevant impact of each component of MS on the risk for the incidence of adverse events in a cohort of essential hypertensives. Design and method: We followed up for a median period of 40 months (IQR 28–60 months) 2176 essential hypertensives free of cardiovascular disease (mean age 57.6 years, 1010 males, office blood pressure (BP) = 143.4/89.2 mmHg). All subjects had at least one annual visit and at baseline underwent complete echocardiographic study for estimation of left ventricular mass index and blood sampling for assessment of metabolic profile and glomerular filtration rate. MS was defined according to the updated NCEP III criteria. Endpoint of interest was the incidence of stroke, coronary artery disease (CAD) and their composite. Results: MS was present at baseline in 819 hypertensives (37.6%) and DM in 305 (14%). The incidence of the composite end-point was 3.1% (20 patients with stroke, 50 with CAD, 2 with both) over the whole follow-up period. Patients with DM were more likely to experience the composite event in comparison to reference category (5.9% versus 1.9%, log rank p < 0.001) or MS (5.9% versus 3.7%, log rank p = 0.018). Patients with MS were more likely to experience the event of interest in comparison to reference category (3.7% versus 1.9%, log rank p = 0.024). When Cox regression models were implemented, MS predicted the composite end-point (HR = 1.94, 95% CIs 1.42–2.67, p < 0.001). MS remained a significant independent predictor after multivariable adjustment for age, gender, left ventricular hypertrophy, glomerular filtration rate and hypertension pattern. When individual components of MS were consecutively inserted into the final multivariable model instead of MS per se, none of them predicted independently the endpoint. Increased triglycerides were associated with increased incidence of composite endpoint but when adjustment for additional confounders was performed this association rendered not significant. Conclusions: Metabolic syndrome predicts independently from its components adverse events in essential hypertensive subjects.